2022
DOI: 10.1017/bap.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Navigating norms and invisible rules: Explaining the case of business influence in international shipping regulation

Abstract: This article develops a micro-level theoretical perspective of business influence in international negotiations. By drawing on organizational institutional theory, the article proposes that site-specific institutionalized norms can structure the nature and extent of business power. The article illustrates the value of this perspective through an illustrative case study of the International Maritime Organization (IMO) through interviews and participant observation of on-site dynamics during negotiations on envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This ethnographic research has provided me with an understanding of the language, procedure and norms at the IMO that are crucial to interpreting the data. As other literature has discussed, the IMO is an organization with many traditions and norms [14,38] that influence the process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This ethnographic research has provided me with an understanding of the language, procedure and norms at the IMO that are crucial to interpreting the data. As other literature has discussed, the IMO is an organization with many traditions and norms [14,38] that influence the process.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature shows scholars have explored the multi-level or polycentric governance nature of maritime policy [9], some with a direct focus on shipping [8,18,[23][24][25][26][27]. Previous research also noted the industry influence in this multi-actor governance at the IMO [11,12,15] and further explored the changing authority and/or policy, with some seeking to explore the changing role of authority and the state [8,27] or the actions of the EU [28,29], and others seeking to explore new actors as policy entrepreneurs [13]. In regard to the IMO specifically, the research agrees that there is considerable industry involvement, and the power has been shown to be concentrated in the hands of a few states and non-state actors.…”
Section: Recent Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those successful in making such claims rely on different sources of influence to create common projects within and between ecologies, or to rebuff ecologies that may contend for jurisdiction. Expert groups provide a microcosm of “problem‐solving collections of actors seeking to produce solutions” (Block‐Lieb & Halliday, 2017, p. 47; see also Hendriksen, 2022).…”
Section: Introductionmentioning
confidence: 99%